Single dose prophylactic antibiotic before surgery to prevent surgical site infection: a prospective interventional study - Saravanan, K.; Uma Maheswari, T. (International Surgery Journal, 2019)
Background: Surgical site infections (SSI) are one of the most common postoperative complications leading to increased morbidity which also an important factor of increased hospital stays and increased healthcare cost. The use of prophylactic antibiotics may benefit the patients in preventing the surgical site infection. Aim of the study was to study the single dose prophylactic antibiotic use in preventing surgical site infection in elective surgery. Methods: Patients were included from the list of elective surgery. Patient with comorbid was excluded. The patient was handled as per NICE guideline for prevention of surgical site infection and treatment 2017. Prophylactic antibiotic injection cefuroxime 1500mg administered intravenously 30 minutes before surgery, at the site of the incision. Results: In 110 patients included in the study, 46% of patients were in 35 to 45 years, male were higher in number. 20% of patients underwent hernioplasty followed by cholecystectomy 18.3%. 9% of SSI was recorded in this study. 4 cases in cholecystectomy, 3 cases in hernioplasty, each 1 case in appendicectomy, Hydrocele and ventral hernia mesh repair. The most common bacteria isolated from the samples were Staphylococcus aureus. Conclusions: In uncomplicated surgeries, single dose antibiotics before 30 minutes of surgery may benefit in preventing SSI.